Introdução à interação de raios-X com a matéria e dicroísmo linear magnético: Aplicação a filmes finos antiferromagnéticos sob deformação - Amorim, Gabriel Alcântara (2024)
This work falls within the context of studying antiferromagnetic thin films subjected to structural deformations and the application of synchrotron light techniques to relate changes in the crystal structure (probed by X-ray diffraction) to the spin orientation of the films (probed by X-ray absorption, the focus of this work). A review is made of classical and quantum theories describing light absorption by matter in the X-ray energy range. Starting from Fermi’s golden rule, from first principles, it is possible to calculate the transition probability between electronic levels of a material as a function of the energy of the incident radiation, allowing an estimate of X-ray beam absorption as a function of its energy. Another point of emphasis is the dependence of light absorption on the sample orientation and the polarization of the incident beam, this property is called dichroism. In particular, X-ray Magnetic Linear Dichroism (XMLD) is the main probing tool for materials with antiferromagnetic ordering, as studied in this work. In XMLD analysis, the difference between X-ray absorption spectra obtained for different orientations between the (linear) polarization of the incident beam and the sample is performed. A Python data analysis tool was then developed to normalize, flattering, display the graphs, and obtain the XMLD signal. The program was compared with Athena software, a well-established tool in the X-ray absorption community, and presented consistent results. The sample consists of a thin antiferromagnetic cobalt oxide (CoO) film, prepared by reactive magnetron sputtering on a flexible cross-shaped substrate. Temperature changes and deformation are applied to the sample and analyzed by XMLD. Controlled deformations are applied by the bidimensional multi-analysis strain instrument (2D-MASI), being used for the first time at SIRIUS. Pre-straining of the substrate before deposition allows for the contraction of the CoO crystal structure. To go below the Neel temperature, which is around room temperature, a nitrogen flux (cryojet) was used. This deformation can alter the sample’s spin orientation (Neel vector) and consequently its absorption spectrum. Finally, a change in absorption measurements is observed after deformation.